GP173 Usage of probiotics in the treatment of gastroenteritis in the paediatric population – a systematic review. (June 2019) - Bell, Allison; Boochoon, Laken; Duffy, Craig; Foo, Jia Jun; Koscic, Sarah; Ozoani, Nnedimma; Rahman, Abidur; Tan, Darolyn; Molloy, Eleanor
Abstract : Background: Acute gastroenteritis is defined as a sudden onset of diarrhoea which in itself is the passage of 3 or more loose stools in a 24 hour period, or the passage of one or more bloody stools in the presence or absence of abdominal pain, fever, nausea and vomiting. Acute gastroenteritis is self-limiting lasting no longer than 2 weeks, however, it is a major cause of morbidity and mortality worldwide. Current primary treatment modalities include restoration of the acid-base balance, correction of electrolyte disturbances, and oral rehydration therapies. The aforementioned therapeutic regimens help to decrease morbidity and mortality, however, it seldom has an impact on the duration of the infection and its symptoms. Probiotics are believed to help reduce both the duration and severity of symptoms of gastroenteritis, however strain specific efficacy and inter-strain comparison has not yet been established. Objective: The aim of this systematic review was to examine established original research to determine the efficacy of probiotics in treating acute gastroenteritis in the paediatric population. We examined the different strains of probiotics utilized and their associated outcomes in treating gastroenteritis. Methods: An Embase search was carried out with the help of a medical librarian. Two independent reviewers screened title and abstract, followed by full text review using the programme Covidence. All reviewer conflicts were resolved by a third party. Data was extracted from the included articles to determine correlation and effects of probiotics. Results: Of the 581 results obtained from the search, 11 studies were included for data extraction after applying the inclusion and exclusion criteria. Majority of the studies showed probiotics reduced duration of diarrhoea (8 of 11 studies), and a reduced duration of hospitalisation (6 of 11 studies). Notably, 2 papers reported adverse effects, such as fungaemia, in immunocompromised and ICU patients. The different strains of probiotics that were examined in the selected papers include Saccharomyces boulardii, Lactobacillus casei, and Lactobacillus acidophilus. Conclusion: Probiotics reduced the duration diarrhoea symptoms and hospitalization. Usage of probiotics was however accompanied by minimal side effects but not indicated in immunocompromised patients with gastroenteritis. However, further research needs to be conducted to determine the strain specific efficacy and dosage requirements for treatment of gastroenteritis using large scale double blinded randomized control trials.